Methods of Data Reduction for Augmented Reality Aplications - Smiian, K.; Kulishova, N. (ХНУРЭ, 2016)
The intensive hardware and software tools development allow to using a wider range of multimedia and interactive functionalities in different areas of everyday life. One of the potentially interesting directions in IT development is augmented reality. Augmented reality (AR) is the environment with the direct or indirect complement of the real world with the digital data in real time. This is implemented by using computer devices such as tablets, smartphones and other gadgets and includes the specially designed software [1]. Unlike virtual reality in computer games, which is not exist, AR technology aims at enriching the existing environment by the additional information.
Keywords: Methods of Data Reduction; Augmented Reality Aplications